Differences in Defect Distribution Across Scan Strategies in Electron Beam AM Ti-6Al-4V : The fraction and size of pores present in EBM Ti-6Al-4V specimens varies depending on the melting strategy used, whether linear raster melting or point melting - Quintana, María José; O’Donnell, Katie; Kenney, Matthew J.; Collins, Peter C. (My University, 2021)
In recent years, additive manufacturing (AM) has begun to displace traditional manufacturing techniques for specific applications. Notable benefits of AM include reduced times from design to product, an improved buy-tofly ratio, lower waste, and the ability to produce complex geometries[1,2]. An additional benefit of additive manufacturing is the variety of manufacturing processes that span across heat source (e.g., laser, electron beam, plasma), input material type (e.g., powder, wire), atmosphere, and the number of axes of control among others[2-4]. This variability in processing route means that a process can be identified and optimized for a class of products or parts. Despite these various advantages, one of the primary drawbacks of AM processes is porosity within builds, which ultimately reduces the ability of a part to withstand tensile stresses and can lead to premature failure[4-6]. Copyright 2021 ASM International.
Keywords: Ingeniería